Gate-controlled electromechanical backaction induced by a quantum dot - Yuma Okazaki (Nature Portfolio, 2016)
Coupling between quantum structures and mechanical resonators remains a challenge. Here, the authors couple a quantum dot and a piezoelectric microresonator and show that gate-induced single electron transport in the quantum dot enables control of the amplitude of the mechanical response.